Brand Communication Gambo Muba: Sinergi Perlindungan Hak Merek dan Pelestarian Warisan Budaya - Septa, Septa; Dirmansyah, Dirmansyah; Muhammad Rasyid Ridlo; Rahmatika Luthfiana Sholikhah (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the legal protection of trademark rights for Gambo Muba, a traditional textile originating from Musi Banyuasin, South Sumatra, as a means of preserving Indonesia’s cultural heritage. Gambo Muba is a unique jumputan batik dyed with gambier resin, a natural byproduct of local agriculture, which not only reflects local wisdom but also contributes to the regional economy. However, without adequate intellectual property protection, such cultural assets are vulnerable to misuse, imitation, and claims by external parties. The research employed an empirical legal approach by combining primary data from interviews with local government representatives and stakeholders managing Gambo Muba, along with secondary data from official documents, legal regulations, and archival sources provided by the Directorate General of Intellectual Property (DJKI). Data collection was conducted through interviews, documentation, and observation, while data analysis was performed using reduction and interpretation techniques to highlight the challenges and achievements in the trademark registration process. The findings reveal that the local government of Musi Banyuasin has successfully registered the trademark Gambo Muba with DJKI under Class 24 (textiles and textile goods). The registration process, which began in November 2021, culminated in official recognition in October 2022, granting legal protection valid until 2031. This achievement provides legal certainty, prevents unauthorized claims, and strengthens the branding of Gambo Muba as a distinctive cultural product. Furthermore, community awareness of the importance of trademark rights has significantly increased, with 98% of respondents acknowledging the role of trademarks in enhancing product competitiveness and safeguarding cultural identity. Despite this success, several challenges remain, including limited funding, complex administrative procedures, and low public understanding of intellectual property rights. These factors hinder broader participation in trademark protection efforts. Nonetheless, the protection of Gambo Muba through trademark registration represents a crucial step toward preserving intangible cultural heritage while promoting sustainable economic development for local communities.